VIDEO PROFIL SEBAGAI SARANA PROMOSI MEMAJUKAN WISATA ALAM KALIBIRU DAN PENINGKATAN EKONOMI MASYARAKAT - Muhfiatun; Rahayu Dwi Saputri; Lailatis Syarifah (UIN Sunan Kalijaga, 2021)
Kali Biru is a natural tourism in an incised hilly area with the background of the Sermo Reservoir. In Kali Biru, tourists will have an interesting experience and be able to take pictures in instagramable photo spots, for example bicycle spots, hang gliding spots, flying fox, and high ropes. For reaching Kali Biru, people can use a tourist jeep via Sermo and Clereng Reservoir routes. However, tourism rebranding efforts on social media are still lacking. Although various attempts have been made. The purpose of designing this media is to create and design a company profile that can provide data, information and products offered by Padukuhan Kali Biru in an effective, clear and attractive manner. In addition, it can increase the brand image and hopefully in turn it can attract the target market, namely new tourists, both local and foreign tourists, to the Kali Biru Nature Tourism offered. Data collection was carried out through documentation in the photos and videos in the field, which was also supported by data from the internet. This product is an interactive video with a modern design style concept, consisting of some menu pages based on the content requirements.